Case Report: Efficacy of Rituximab in a Patient With Familial Mediterranean Fever and Multiple Sclerosis - Pozzato, Mattia; Micaglio, Emanuele; Starvaggi Cucuzza, Chiara; Cagol, Alessandro; Galimberti, Daniela; Calandrella, Daniela; Cinnante, Claudia; Pappone, Carlo; Zanussi, Monica; Meola, Giovanni; Scarpini, Elio; Bresolin, Nereo; et al. (Frontiers in Neurology, 2021)
Familial Mediterranean Fever (FMF) is a genetic autoinflammatory disease characterized by recurrent episodes of fever and serositis caused by mutations in the MEFV gene, while Multiple Sclerosis (MS) is an inflammatory demyelinating disease of the CNS with genetic and environmental etiology. The two diseases rarely occur in association with relevant implications for clinical management and drug choice. In this paper, we present the case of a 53-year-old male with an autosomal dominant FMF since childhood who presented acute paresthesia at the right part of the body. He performed a brain and spinal cord MRI, which showed multiple brain lesions and a gd-enhancing lesion in the cervical spinal cord, and then received a diagnosis of MS. He then started Interferonβ-1a which was effective but not tolerated and caused hepatotoxicity, and then shifted to Rituximab with 3-month clinical and neuroradiological efficacy.